Analisis Fisikokimia, Aktivitas Antioksidan, dan Sensoris dari Ekstrak Daun Sungkai (Peronema canescens Jack.) - Devi Silsia; Syafnil; Laili Susanti; Marniza; Tomi Tri Rachmadi (Faculty of Forestry Universitas Gadjah Mada, 2024)
Sungkai leaves were widely used as an immunomodulatory agent during the COVID-19 pandemic. This research aimed to determine the color, phytochemical characteristics, vitamin C content, polyphenol content, antioxidant activity, and sensory of sungkai leaves extracts from various types of leaves (shoot, young, and old) as well as the condition (fresh and dry). The extraction process included boiling the sample with water at a temperature of 90⁰C for 10 minutes. The parameters observed in this study were color, phytochemicals screening, vitamin C, polyphenols, antioxidant activity, and sensory. The results showed that the extract color was influenced by the types of leaves. These included red-purple for the shot leaves and yellow for young and old leaves. The extract contained flavonoids, tannins, and saponins. The fresh leaves extract produced a higher total vitamin C, polyphenols, and antioxidant activity compared to the dry counterparts. Furthermore, the highest chemical content of sungkai leaves extract was discovered in fresh shoot leaves with total vitamin C, polyphenols, and IC50 values of 172.77 μg/ml, 280.77 μg/ml, and 28.33 μg/ml (strong antioxidant activity), respectively. Sensory characteristics of color, aroma, taste, and overall taste in each extract differed in liking score. Overall, panelists preferred the extract from dried older leaves.